A novel DREB transcription factor enhances salt tolerance in peanut (Arachis hypogaea L.) through upregulation of AhP5CR and AhBADH, leading to increased osmolyte accumulation - Thuy Thi Xuan Vi; Linh Thi Dieu Nguyen; Tuong Manh Ho; Quan Huu Nguyen; Lan Thi Ngoc Nguyen; Mau Hoang Chu (Molecular Biology Reports, 2026)

Chitosan nanoparticles derived from molted shrimp shells as biodegradable adjuvants for Vibrio harveyi vaccination in Asian sea bass (Lates calcarifer) - Tran Vi Hich; Khuong V. Dinh; Nguyen Thi Kim Cuc; Nguyen Thi Thuy Giang; Pham Thi Dan Phuong; Nguyen Cong Minh; Trang Si Trung (Regional Studies in Marine Science, 2026)

Covalently crosslinked amine-functionalized carbon nanotubes with MXene based cellulose nanofiber lamellae structure for thermoconductive electromagnetic interference shielding materials with enhanced stability and flame retardancy - Chi Thien Nguyen; Tien Thi Cam Vo; Thanh Tung Duong; Thi Tuong Vi Tran; Truong Son Le Vu; Trinh Ngoc Dat; Mai Thi Kieu Lien; Duy Khiem Nguyen; Minh Canh Vu (Chemical Engineering Journal, 2026)

Leakage-controlled machine learning for European Cd, Hg, and Pb emission inventories - Tianyi Guan; Jennifer Uyen-Vi Nguyen (Environmental Monitoring and Assessment, 2026)

Integrated valorization of durian rind into bioactive carboxymethyl cellulose hydrogels: Co-recovery of flavonoids and cellulose with physicochemical, functional, and economic evaluation - Thi Cam Vi Nguyen; Hoai Khang Tran; Thi Kim Chi Nguyen; Tien-Ngo Van; Vinh Tran Phuc Nguyen; Boi Tuyen Ly; Dieu-Hien Truong; Colin J. Barrow; Hoang Chinh Nguyen (Food Hydrocolloids, 2026)

Inside from outside: head-to-skull-and-muscles translation with statistical shape relation and multiple region-of-interest learning - Tan-Nhu Nguyen; Trung-Nhat Nguyen; Vi-Do Tran; Trieu-Nhat-Thanh Nguyen; Marie-Christine Ho Ba Tho; Tien-Tuan Dao (Medical & Biological Engineering & Computing, 2026)

Bridging the Social Gap Between Circular Economy and Human Development: A Semi-Systematic Review Through the Lens of Capability Approach - Minh Ngoc Dao; Thi Hoai Le Nguyen; Khanh Vi Nguyen; Hong Quan Nguyen; Hoang Ha Vu (Circular Economy and Sustainability, 2026)

First genomic insights into multidrug-resistant Staphylococcus pseudintermedius from dogs in Vietnam - Nguyen Thi Lan Anh; Luu Thi Thanh Hang; Doan Thi Kim Cuc; Nguyen Thuy Y Vi; Dao Huyen Tran; Pham Phan My Tien; Farhid Hemmatzadeh; Lam Thanh Nguyen (Comparative Immunology, Microbiology and Infectious Diseases, 2026)

Rice husk-derived silica aerogel/chitosan nanocomposite for electrochemical determination of thiomersal in vaccines and ophthalmic drugs - Cam Vi Dao Thi; Tuan Anh Nguyen; Thuy Ngan Doan; Quang Minh Pham; Anh-Tuan Vu (Environmental Nanotechnology, Monitoring & Management, 2026)

Spatial and seasonal changes in levels of perfluoroalkyl acids (PFAAs) in surface water and sediment from a typical paper-recycling area in Vietnam - Thi Vi Phung; Thuy Ngoc Nguyen; Thanh Dam Nguyen; Dinh Quang Phan; Huu Tuyen Le; Hung Viet Pham; Hong Anh Duong (Environmental Geochemistry and Health, 2026)

Hydroclimatic variability and household resilience in a mountain lake tourism destination: a case study of Ba Be National Park, Vietnam - Thi Bich Lien Nguyen; Quoc Lap Kieu; Thanh Huy Chu; Duy Minh Dao; Thi Ngoc Ha Tran; Thuy Linh Vi; Thi Bich Hanh Nguyen (Theoretical and Applied Climatology, 2026)

Electrochemically synthesized graphene@ZnO@MnO2 composite as an advanced adsorbent for levofloxacin removal - Le Phuong Hoang; Thi Thao Truong; Van-Truong Nguyen; Nguyen Thi Thuy Hang; Thi Mai Huong Vi; Duy-Hung Mac; Thi Kim Dung Hoang; Nguyen Tran Hung; Thao Tran Thi Bich (Environmental Science and Pollution Research, 2026)

Vascular Organoids Derived from Capillary malformation-induced Pluripotent Stem Cells Exhibit Disease-Relevant Phenotypes - Vi Nguyen; Anna Harper; Mackenzie Azuero; Isabella Castellanos; Siwuxie He; Marcelo L. Hochman; Camilla F. Wenceslau; Dong-bao Chen; Anil G. Jegga; Yunguan Wang; Daping Fan; J. Stuart Nelson; et al. (Stem Cell Reviews and Reports, 2026)
Capillary malformation (CM) is a congenital vascular anomaly that affects the skin, mucosa, eye, and brain. A major obstacle to mechanistic and drug screening studies for CM has been the lack of preclinical models. In this study, we established vascular organoids (VOs) generated through the self-assembly of vascular lineages of endothelial cells and smooth muscle cells differentiated from CM-induced pluripotent stem cells (iPSC). Within these VOs induced endothelial cells and smooth muscle cells organized into juxtapositions to form vascular branches. CM patient iPSC-derived VOs showed a higher density of endothelial and smooth muscle cell populations and greater vascular branch lengths as compared with VOs derived from iPSCs generated from healthy skin biopsies. Overall, this study represents the first disease-relevant VO model of CM, providing a valuable platform for future mechanistic studies and drug screening.

Oleaginous yeasts as a sustainable alternative source of lipids: an investigation into microbial isolation from food sources, fermentation kinetics, fatty acid profiles, and potential health benefits of microbial lipids - Quoc Duy Nguyen; Thi-Van-Linh Nguyen; Thi Tuong Vi Tran; Yunus Khatri; Jayani Chandrapala; Tuyen Truong (Biocatalysis and Agricultural Biotechnology, 2025)

Correction to: Stem Cell Markers LGR5, LGR4 and Their Immediate Signalling Partners are Dysregulated in Preeclampsia - Georgia P. Wong; Sunhild Hartmann; Olivia Nonn; Ping Cannon; Tuong-Vi Nguyen; Manju Kandel; Natasha de Alwis; Ciara N. Murphy; Natasha Pritchard; Ralf Dechend; Natalie J. Hannan; Stephen Tong; et al. (Stem Cell Reviews and Reports, 2025)

Enhancing anti-inflammatory activity of noni (Morinda citrifolia L.) juice using lactic acid fermentation by Leuconostoc lactis for developing fermented noni microcapsules as a novel nutraceutical supplement - Thanh-Thuy Dang; Thi-Van-Linh Nguyen; Thi Tuong Vi Tran; Vinh-Lam Nguyen; Quoc-Trung Huynh; Anh Duy Do; Phuoc-Bao-Duy Nguyen; Quoc-Duy Nguyen (Biocatalysis and Agricultural Biotechnology, 2025)

Fermentation of Ngoc Linh ginseng (Panax vietnamensis Ha et Grushv.) root extract using Levilactobacillus brevis QD-1: Changes in majonoside R2 content and pharmacological activities - Quoc-Duy Nguyen; Thi-Van-Linh Nguyen; Thi Tuong Vi Tran; Ngoc-Han Ngo-Thi; Hong-Tham Truong-Thi; Vinh-Lam Nguyen; Trong Khoa Luong; Anh Duy Do (Food Research International, 2025)

Stem Cell Markers LGR5, LGR4 and Their Immediate Signalling Partners are Dysregulated in Preeclampsia - Georgia P. Wong; Sunhild Hartmann; Olivia Nonn; Ping Cannon; Tuong-Vi Nguyen; Manju Kandel; Natasha de Alwis; Ciara N. Murphy; Natasha Pritchard; Ralf Dechend; Natalie J. Hannan; Stephen Tong; et al. (Stem Cell Reviews and Reports, 2025)

Trophoblast Side-Population Markers are Dysregulated in Preeclampsia and Fetal Growth Restriction - Georgia P. Wong; Sunhild Hartmann; David G. Simmons; Sarah Ellis; Olivia Nonn; Ping Cannon; Tuong-Vi Nguyen; Anna Nguyen; Lucy A. Bartho; Stephen Tong; Natalie J. Hannan; Tu’uhevaha J. Kaitu’u-Lino (Stem Cell Reviews and Reports, 2024)
Dysregulated progenitor cell populations may contribute to poor placental development and placental insufficiency pathogenesis. Side-population cells possess progenitor properties. Recent human trophoblast side-population isolation identified enrichment of 8 specific genes ( CXCL8, ELL2, GATA6, HK2, HLA-DPB1, INTS6, SERPINE3 and UPP1 ) (Gamage et al. 2020, Stem Cell Rev Rep ). We characterised these trophoblast side-population markers in human placenta and in placental insufficiency disorders: preeclampsia and fetal growth restriction (FGR). Trophoblast side-population markers localised to mononuclear trophoblasts lining the placental villous basement membrane in preterm control, preeclamptic and FGR placental sections ( n = 3, panel of 3 markers/serial section). Analysis of single-cell transcriptomics of an organoid human trophoblast stem cell (hTSC) to extravillous trophoblast (EVT) differentiation model (Shannon et al. 2022, Development ) identified that all side-population genes were enriched in mononuclear trophoblast and trophoblasts committed to differentiation under hTSC culture conditions. In vitro validation via 96 h time course hTSC differentiation to EVTs or syncytiotrophoblasts ( n = 5) demonstrated ELL2 and HK2 increased with differentiation ( p < 0.0024, p < 0.0039 respectively). CXCL8 and HLA-DPB1 were downregulated ( p < 0.030, p < 0.011 respectively). GATA6 and INTS6 increased with EVT differentiation only, and UPP1 reduced with syncytialisation. SERPINE3 was undetectable. Trophoblast side-population marker mRNA was measured in human placentas (< 34-weeks’ gestation; n = 78 preeclampsia, n = 30 FGR, and n = 18 gestation-matched controls). ELL2, HK2 and CXCL8 were elevated in preeclamptic ( p = 0.0006, p < 0.0001, p = 0.0335 respectively) and FGR placentas ( p = 0.0065, p < 0.0001, p = 0.0001 respectively) versus controls. Placental GATA6 was reduced in pregnancies with preeclampsia and FGR ( p = 0.0014, p = 0.0146 respectively). Placental INTS6 was reduced with FGR only ( p < 0.0001). This study identified the localisation of a unique trophoblast subset enriched for side-population markers. Aberrant expression of some side-population markers may indicate disruptions to unique trophoblast subtypes in placental insufficiency. Graphical Abstract

Removal of perfluoroalkyl acids (PFAAs) from aqueous solution by water hyacinth (Eichhornia crassipes): Uptake, accumulation, and translocation - Thi Vi Phung; Thanh Dam Nguyen; Thuy Ngoc Nguyen; Thi Kim Truong; Hung Viet Pham; Hong Anh Duong (Science of The Total Environment, 2024)

Extracting phenolics, flavonoids, and terpenoids from Codonopsis pilosula using green solvents - Tan Phat Vo; Minh Thu Ho; Phan Uoc Nguyen Nguyen; Ngoc Duyen Pham; Khanh Vi Truong; Thi Hoang Yen Nguyen; Dinh Quan Nguyen; Thi Thanh Huong Vo (Sustainable Chemistry and Pharmacy, 2024)

Enhancing pharmaceutical wastewater treatment: Ozone-assisted electrooxidation and precision optimization via response surface methodology - Huy N.Q. Phan; Hoang-Jyh Leu; Vi N.D. Nguyen (Journal of Water Process Engineering, 2024)

Retention and export of planktonic fish eggs in the northeastern Gulf of Mexico - Bich Vi Viviane Nguyen; Yonggang Liu; Christopher D. Stallings; Mya Breitbart; Steven A. Murawski; Robert H. Weisberg; Makenzie Kerr; Eva‐Maria S. Bønnelycke; Ernst B. Peebles (Fisheries Oceanography, 2024)
To help determine whether planktonic eggs of fishes on the West Florida Shelf (WFS) are retained locally or exported elsewhere, we collected fish eggs by plankton net from 17 locations (stations) and identified them using DNA barcoding. We then entered the station coordinates into the West Florida Coastal Ocean Model (WFCOM) and simulated the trajectories of the passively drifting eggs over 2 weeks at three depths (surface, midwater, and near bottom). The results indicated there were two groups of trajectories: a nearshore group that tended to be retained and an offshore group that tended toward export and potential long‐distance dispersal. We also found evidence of a relationship between retention and higher fish‐egg abundance; nearshore stations were associated with higher fish‐egg abundances and higher retention. We suggest this is the result of (1) increased spawning in high‐retention areas, (2) increased drift convergence in high‐retention areas, or both processes acting together. Community analysis using SIMPROF indicated the presence of a depth‐related (retention‐related) difference in species assemblages. Fish‐egg species were also categorized as pelagics or non‐pelagics; there was no evidence of pelagic species being more likely to be exported.

Preparation of gelatin/carboxymethyl cellulose/guar gum edible films enriched with methanolic extracts from shallot wastes and its application in the microbiological control of raw beef - Quoc-Duy Nguyen; Thi Tuong Vi Tran; Nhu-Ngoc Nguyen; Tran-Phong Nguyen; Tuyet-Ngan Lien (Food Packaging and Shelf Life, 2023)

Acute and sub-acute toxicity evaluation of Merremia tridentata (L.) stem extract on mice - Em Canh Pham; Lenh Vo Van; Cuong Viet Nguyen; Ngoc Thoi Nguyen Duong; Tuong Vi Le Thi; Tuyen Ngoc Truong (Toxicon, 2023)

Effect of Gradient Descent Optimizers and Dropout Technique on Deep Learning LSTM Performance in Rainfall-runoff Modeling - Duong Tran Anh; Dat Vi Thanh; Hoang Minh Le; Bang Tran Sy; Ahad Hasan Tanim; Quoc Bao Pham; Thanh Duc Dang; Son T. Mai; Nguyen Mai Dang (Water Resources Management, 2023)

Perfluoroalkyl substances (PFAS) in freshwater fish from urban lakes in Hanoi, Vietnam: concentrations, tissue distribution, and implication for risk assessment - Nguyen Thi Quynh Hoa; Tran Thi Lieu; Hoang Quoc Anh; Nguyen Thi Anh Huong; Nguyen Trong Nghia; Nguyen Thi Chuc; Phan Dinh Quang; Phung Thi Vi; Le Huu Tuyen (Environmental Science and Pollution Research, 2022)

Enhanced head-skull shape learning using statistical modeling and topological features - Tan-Nhu Nguyen; Vi-Do Tran; Ho-Quang Nguyen; Duc-Phong Nguyen; Tien-Tuan Dao (Medical & Biological Engineering & Computing, 2022)

A new triterpenoid and other compounds from lichens Cryptothecia faveomaculata Makhija & Patw - Nguyen Ngoc Tuan; Ping-Chung Kuo; Tran Trung Hieu; Le Nguyen Tuong Vi; Quach Tong Hung; Le Tien Dunge; Nguyen Duy Trinh; Nguyen Quang Trung; Nguyen Cuu Khoa; Ha Viet Hai; Tran Dinh Thang (Natural Product Research, 2021)

Humane neuromuskuläre Organoide — Anwendung und Perspektive - Jorge Miguel Faustino Martins; Lan Vi Ngoc Nguyen; Mina Gouti (BIOspektrum, 2021)
Organoids are miniature, organ-like structures derived from stem cells. While techniques for developing organoids for different tissues have advanced in the past decade, it has remained a challenge to simultaneously grow two different tissues into a single functional organoid. We have recently developed a 3D neuromuscular organoid that allows the simultaneous generation of spinal neurons and skeletal muscles. Here we discuss their future applications in modeling neuromuscular disorders.

A statistical shape modeling approach for predicting subject-specific human skull from head surface - Tan-Nhu Nguyen; Vi-Do Tran; Ho-Quang Nguyen; Tien-Tuan Dao (Medical & Biological Engineering & Computing, 2020)

MicroRNA Regulatory Network as Biomarkers of Late Seizure in Patients with Spontaneous Intracerebral Hemorrhage - Ifeanyi Iwuchukwu; Doan Nguyen; Michelle Beavers; Vi Tran; Wale Sulaiman; Erin Fannin; Lindsay Lasseigne; Eugene Ramsay; Jason Wilson; Nicolas G. Bazan (Molecular Neurobiology, 2020)

Neuroendocrine Effects of Lactation and Hormone-Gene-Environment Interactions - Kirsten Gust; Christina Caccese; Amanda Larosa; Tuong-Vi Nguyen (Molecular Neurobiology, 2020)

Cell numbers, distribution, shape, and regional variation throughout the murine hippocampal formation from the adult brain Allen Reference Atlas - Sarojini M. Attili; Marcos F. M. Silva; Thuy-vi Nguyen; Giorgio A. Ascoli (Brain Structure and Function, 2019)

Overexpression of the ZmDEF1 gene increases the resistance to weevil larvae in transgenic maize seeds - Thi Xuan Thuy Vi; Thi Ngoc Lan Nguyen; Thi Thanh Nhan Pham; Huu Quan Nguyen; Thi Hai Yen Nguyen; Quang Tan Tu; Van Son Le; Hoang Mau Chu (Molecular Biology Reports, 2019)

Case Report: A Case of Chromoblastomycosis Caused by Fonsecaea pedrosoi in Vietnam - Tran-Anh Le; Khac-Luc Nguyen; My-Hang Pham; Thuat-Thang Vi; Ngoc-Anh Do (Mycopathologia, 2019)

Genetic mapping and validation of the loci controlling 7S α′ and 11S A-type storage protein subunits in soybean [Glycine max (L.) Merr.] - Jeffrey D. Boehm; Vi Nguyen; Rebecca M. Tashiro; Dale Anderson; Chun Shi; Xiaoguang Wu; Lorna Woodrow; Kangfu Yu; Yuhai Cui; Zenglu Li (Theoretical and Applied Genetics, 2018)

Effects of Sex Steroids in the Human Brain - Tuong-Vi Nguyen; Simon Ducharme; Sherif Karama (Molecular Neurobiology, 2017)

Maternal obesity alters endoplasmic reticulum homeostasis in offspring pancreas - Jumpei Soeda; Angelina Mouralidarane; Paul Cordero; Jiawei Li; Vi Nguyen; Rebeca Carter; Sabrina R. Kapur; Joaquim Pombo; Lucilla Poston; Paul D. Taylor; Manlio Vinciguerra; Jude A. Oben (Journal of Physiology and Biochemistry, 2016)

Two naturally occurring deletion mutants of 12S seed storage proteins in Arabidopsis thaliana - Anfu Hou; Kede Liu; Niramol Catawatcharakul; Xurong Tang; Vi Nguyen; Wilfred A. Keller; Edward W. T. Tsang; Yuhai Cui (Planta, 2005)